(untitled) (International Journal of Pharmaceutical and Life Sciences, 2012)
In the present study, the antioxidant and analgesic potential of the ethanolic extract of the leaves of Derris trifoliata was evaluated. The free radical scavenging activity of the crude extract on the stable radical 1, 1-diphenyl-2-picrylhydrazyl (DPPH) was determined by comparing the DPPH inhibitory capacity of the extract. In the quantitative assay, Derris trifoliata extract displayed a free radical scavenging activity in the DPPH assay (IC50 = 19 ?g/ml) which is comparable to that of ascorbic acid (IC50 = 7.80 ?g/ml), a well-known standard antioxidant. The analgesic responses of the given samples of extracts were evaluated using the Tail immersion method. In the analgesic activity test, extract at dose of 200 mg/kg and 400 mg/kg exhibited significant (P<0.05 and P<0.001 respectively) inhibition of pain by 166.82 and 184.95 after 120 and 180 minutes respectively while the standard drug Diclofenac Na inhibition was found to be 217.67 after 180 minutes at a dose of 25 mg/kg body weight DOI: http://dx.doi.org/10.3329/ijpls.v1i2.12951 International Journal of Pharmaceutical and Life Sciences Vol.1(2) 2012